Kurdish National Identity in a Global Context - AbdulKareem Sherwani, Kawa; Mohammad, Bandar (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
National identity is a broad concept. Anthony Smith (1991) and Shulman (2002) proposed two models and identified some components and elements as the building blocks of national identity. However, they both acknowledge the fact that their lists are not exhaustive and elements can be added or removed to or from the lists. Kurds, as the largest ethnic group without a state in the world, work very hard to establish a unified national identity as it is the first step of nation building. The study aims at the applicability of the two models on Kurds. Apparently, territory, language and culture are huge problems due to the limited access of different parts to others in different times.